The effect of MRI-based screening and selection on the prevalence of syringomyelia in the Dutch and Danish Cavalier King Charles Spaniels - Limpens, Citlalli; Smits, Vivian T. M.; Fieten, Hille; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2024)
Introduction: Syringomyelia (SM) is a heritable disorder causing a fluid filled cavity (FFC) in the spinal cord with a reported overall prevalence in the Cavalier King Charles Spaniels (CKCS) of 39 to 46%. Breeders started screening their CKCS with MRI in the Netherlands since 2004 and in Denmark since 2015. The goal of this study was to evaluate the effect of MRI-based selection in breeding on the prevalence of SM. Method: MRI scans of 2125 purebred CKCS were available. SM was defined as having a visible FFC in the spinal cord. Prevalence of SM per year of birth was calculated and a logistic regression was used to evaluate affected status of offspring from affected versus unaffected parents and age category of the parent. And to study the combined effect of parental status and age-category to evaluate the effect on affected status of the offspring. Results: The mean FFC in affected CKCS was 2.03 ± 1.47 mm and ranged from 0.5 to 9 mm (median of 1.5 mm). An age effect exists as older CKCS have a higher frequency of being affected compared to younger CKCS. There was no significant sex predilection for SM in this dataset. The mean prevalence of SM decreased slightly from 38% (2010-2014; 2.8 ± 1.3 years of age (mean ± sd); median 2.6 years) to 27% (2015-2019; 2.4 ± 1.2 years of age; median 2.1 years) in the screened population of CKCS (p= 4.3e-07). Breeding with 2 affected parents increased the Odds ratio for producing affected offspring with 3,08 (95% CI 1.58-6.04) compared to breeding with unaffected parents. Discussion: MRI-based screening and selection against SM led to a minimal decrease in prevalence of SM in the Dutch and Danish CKCS population. Breeding with dogs with SM significantly increases the risk of affected offspring. As the disorder is progressive with age, and based on the results of this study, MRI-based screening for all CKCS is recommended at an age of 3 years or older, and to reduce SM more effectively, CKCS affected with SM should not be used for breeding.